2014
DOI: 10.1111/jgh.12507
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization versus surgery/radiofrequency ablation for recurrent hepatocellular carcinoma with or without microvascular invasion

Abstract: TACE may be the more effective treatment option for recurrent HCC of BCLC stage 0 or A than surgery/RFA in MVI-positive patients, especially in those that recur early after curative resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 29 publications
0
28
1
Order By: Relevance
“…They revealed that TACE provided significantly better overall survival among early (≤12 months) recurrent MVI-positive patients than surgery/RFA after curative resection for HCC (52). However, they suggested that a large-scale study is needed to confirm the results of their study.…”
Section: Locoregional Treatmentmentioning
confidence: 70%
“…They revealed that TACE provided significantly better overall survival among early (≤12 months) recurrent MVI-positive patients than surgery/RFA after curative resection for HCC (52). However, they suggested that a large-scale study is needed to confirm the results of their study.…”
Section: Locoregional Treatmentmentioning
confidence: 70%
“…26 These findings are somewhat contradicted by a recently published study that found TACE superior to resection and RFA for recurrent HCC after resection in patients who were found to have microvascular invasion at the primary resection. 27 However, close inspection of this manuscript reveals that the resection/RFA group had a nearly 30% perioperative mortality for the entire cohort and a nearly 50% perioperative mortality for the group with microvascular invasion that was found to be inferior to TACE. These findings highlight the fact that surgical treatments for HCC offer benefit over other modalities only if they can be performed with minimal risk of procedure-related mortality.…”
Section: Discussionmentioning
confidence: 96%
“…TACE is reported to be more effective than surgery or RFA in patients with early recurrence and MVI after curative resection, staged as BCLC 0 or A (35). Despite its retrospective setting, lack of randomization and small sample size, this article contributed to the discussion on which treatment should be preferred for recurrent HCCs as a bridge to salvage transplantation.…”
Section: Discussionmentioning
confidence: 98%
“…In 2014, Jin and colleagues in their retrospective study reported the outcomes of 68 patients who underwent either TACE or surgery/RFA for recurrent HCC after an initial surgical approach (35). Cumulative overall survival rates at 1, 3, and 5 years after re-treatment were 65.1%, 27.9% and 18.6%, respectively, in the surgery/RFA group, and 91.2%, 66.1% and 30.0%, respectively, in the TACE group (p=0.23).…”
Section: Ablative Therapies: Radiofrequency Ablation (Rfa) -Percutanementioning
confidence: 99%